Edukasi Perilaku Hidup Sehat Melalui Kebiasaan Sehari-Hari pada Anak di Desa Jatisari - Fatihatul Qolby; Shella Novitasari; Erina Adriana Paramitha; Renaya Amelta Sahda; Zaenal Muttaqqin; Putri Kinasih; Mutiara Bahi Almayda; Annisa Nur Syahadah; Muhammad Rafi Ammar (Community: Jurnal Pengabdian Kepada Masyarakat, 2022)
Early childhood is an individual who is experiencing a fundamental development process for his future life. Therefore, various things that are received by children at an early age will become the basic foundation for their future life. Health is one of the main and very important factors in child development. When a child's health condition is not healthy, it will have an impact on various things related to his development and on the various activities he will carry out. Implementation of Clean and Healthy Behavior (PHBS) is a set of behaviors that are practiced on the basis of awareness as a result of learning. The learning carried out aims to make children able to help themselves in the health sector. In addition, this pattern (PHBS) aims to motivate children to play an important role in realizing physical health or body health.